Liquid oil-in-water composition
By using a specific anion surface active agent and adjusting emulsion drop particles by using specific anion surface active agents in water -based oily compositions to form a α gel film structure, solving the viscosity and stability of emulsification and stability of the existing technology in the existing technology The problem of insufficient sexuality realizes the stability and application of liquid cosmetics.
Patent Information
- Application Number
- CN202080036679.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-17
- Filing Date
- 2020-05-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-05-15
AI Technical Summary
When the oil-in-water emulsification compositions are increased, the oil-in-water emulsification compositions are prone to problems of time separation or emulsification, and their viscosity stability is insufficient, making them difficult to apply to liquid cosmetics.
Through relative to straight saturated alcohol, a specific octopus surface active agent is used, such as N-steely-N-sodium taper taarate or N-hard fatty-l-glutamic acid and its salt, and its salt Adjust the particle size of the emulsion drip below 160nm, forming an α gel film structure that is covered with emulsion droplets.
The long -term viscosity stability and emulsification stability of liquid water -based oil -type composition are realized, and separation and milk analysis are avoided, and the application of liquid cosmetics is suitable for the application of liquid cosmetics.
Smart Images

Figure CN113811283B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid oil-in-water composition, and more particularly to a liquid oil-in-water composition which is excellent in viscosity stability and emulsification stability over time despite being in a liquid state. Background Art
[0002] Conventionally, when the content of the oil in water-in-oil type composition is increased, there is a problem that the emulsion stability decreases due to separation or creaming over time. In response to this, attempts have been made to improve the emulsion stability by using the alpha gel, such as a technique of blending a hydrophilic anionic surfactant and a higher aliphatic alcohol at a predetermined molar ratio to form an alpha gel having a gel transition temperature of 60° C. or higher (Patent Document 1), or a technique of preparing an alpha gel intermediate composition having a bicontinuous microemulsion phase composed of a mixture of a higher alcohol and anionic surfactant mixed at a predetermined molar ratio and a mixture of a water-soluble solvent having a specific IOB value and water mixed at a predetermined mass ratio, adding a heated oil component to the composition, and then adding water and stirring to induce the formation of an alpha gel, etc. (Patent Document 2).
[0003] Alpha gel is one of the self-organized bodies formed by amphiphilic substances. It is located between solid hydrated crystals (coacervate) and lamellar liquid crystals. It is in a state of maintaining a large amount of water between its hydrophilic groups while maintaining a crystalline state. Crystals that can hardly hold water, such as coacervate, are in a state where the molecules themselves are tilted and packed more tightly. In contrast, the structure of the bimolecular membrane of lamellar liquid crystal is rich in fluidity and is in a liquid state, so it can hold a large amount of water. In alpha gel, the surfactant is arranged in layers in the same way as lamellar liquid crystals, but because it is regularly filled in hexagonal crystals, although rotational motion is maintained, the mobility of the hydrophobic groups is insufficient compared to lamellar liquid crystals, and the movement of the molecules is controlled. If the difference in mobility based on such a structure is observed by differential scanning calorimetry (DSC), heat transfer as a gel-liquid crystal phase transition can be observed.
[0004] However, since α gel is an intermediate phase between lamellar liquid crystal and coacervate, it is generally unstable, and the oil-in-water emulsion composition containing α gel obtained by the techniques of the above-mentioned Patent Documents 1 and 2 may lack viscosity stability, such as viscosity increasing over time. In addition, the techniques of the above-mentioned Patent Documents 1 and 2 are techniques for providing emulsion stability based on the thickening effect of α gel, and since the viscosity is relatively high immediately after preparation, it is difficult to apply the techniques to liquid cosmetics such as lotions.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2001-348325
[0008] Patent Document 2: Japanese Patent Application Publication No. 2016-14011
[0009] Non-patent literature
[0010] Non-patent document 1: J. Soc. Cosmet. Chem. Jpn. 30 (3) 310-320 (1996),
[0011] Non-patent document 2: Food Biophysics, September 2012, Vol. 7, No. 3, pp. 227-235,
[0012] Non-patent document 3: J. Soc. Cosmet. Chem. Jpn. 44 (2) 103-117 (2010). Summary of the invention
[0013] Problems to be solved by the invention
[0014] An object of the present invention is to provide an oil-in-water emulsion composition which is excellent in viscosity stability and emulsification stability over time despite being in a liquid state.
[0015] Means of solving problems
[0016] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that by combining a specific anionic surfactant such as sodium N-stearoyl-N-methyltaurate or N-stearoyl-L-glutamic acid and a salt thereof in a predetermined amount with respect to a linear saturated higher alcohol, and adjusting the particle size of the formed emulsion droplets to 160 nm or less, the viscosity does not increase over time, and the liquid state can be maintained for a long time after the preparation, and a good emulsified state can be stably maintained without causing creaming or separation, thereby completing the present invention.
[0017] That is, the present invention is a liquid oil-in-water composition, which contains the following components (A) to (C):
[0018] (A) a straight-chain saturated higher alcohol having 16 or more carbon atoms,
[0019] (B) at least one anionic surfactant selected from sodium N-stearoyl-N-methyltaurate, N-stearoyl-L-glutamic acid and salts thereof,
[0020] (C) Liquid oil;
[0021] The molar ratio (A / B) of component (A) to component (B) is 2.8 to 6, and the mass ratio ((A+B) / C) of the total of components (A) and (B) to component (C) is 0.3 to 0.75.
[0022] The average emulsified particle size is 160 nm or less.
[0023] Effects of the Invention
[0024] The oil-in-water emulsion composition of the present invention is liquid, but has excellent viscosity stability and emulsification stability over time, can maintain liquid properties for a long time without viscosity increase, and can stably maintain a good emulsified state without creaming or separation. In addition, when the composition contains an oil-soluble active ingredient, its stability over time can be improved, and the effect of the active ingredient can be stably maintained. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] [ Figure 1 ] This is a graph showing the results of differential scanning calorimetry (DSC) of the compositions having average emulsified particle sizes of 80 nm, 110 nm, 170 nm, and 1 μm in Test Example 1.
[0026] [ Figure 2 ] A diagram showing the X-ray diffraction results of the compositions having average emulsified particle sizes of 80 nm and 110 nm in Test Example 1.
[0027] [ Figure 3 ] This is an electron micrograph of the composition in Test Example 1 having an average emulsified particle size of 110 nm.
[0028] [ Figure 4 ] Electron micrograph of the liposome in Reference Example 1. DETAILED DESCRIPTION
[0029] As the straight-chain saturated higher alcohol with 16 or more carbon atoms as component (A), for example, cetyl alcohol, cetearyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, wood wax alcohol, wax alcohol, etc. can be listed, and one or more of them can be used. Among them, from the viewpoint of viscosity stability and emulsion stability, cetearyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, etc. are preferred, and cetearyl alcohol and stearyl alcohol are particularly preferred. From the viewpoint of viscosity stability and emulsion stability, the content of component (A) in the oil-in-water composition of the present invention (hereinafter sometimes referred to as "composition") is preferably 0.5~2 mass % (hereinafter referred to as "%"), more preferably 1~1.7%.
[0030] Component (B) is sodium N-stearoyl-N-methyl taurate, N-stearoyl-L-glutamic acid and its salt as an anionic surfactant. As N-stearoyl-L-glutamate salt, sodium salt, potassium salt, magnesium salt, etc. can be listed, and one or more of them can be used. Among them, from the viewpoint of viscosity stability and emulsification stability, sodium N-stearoyl-N-methyl taurate, N-stearoyl-L-glutamic acid, and disodium N-stearoyl-L-glutamate are preferred. From the viewpoint of viscosity stability and emulsification stability, the content of component (B) in the composition of the present invention is preferably 0.4~1%, more preferably 0.5~0.9%.
[0031] The liquid oil of component (C) may be used without particular limitation as long as it is an oil that is liquid at room temperature (25° C.), and examples thereof include hydrocarbons such as isododecane, isohexadecane, light isoparaffin, liquid paraffin (mineral oil), squalane, squalene, α-olefin oligomers, polybutene, liquid isoparaffin, heavy liquid isoparaffin, polyisobutene, and hydrogenated polyisobutene, and rapeseed oil, avocado oil, almond oil, apricot kernel oil, perilla seed oil, orange oil, olive oil, kiwi seed oil, sesame oil, wheat germ oil, rice germ oil, rice bran oil, safflower oil, sage oil, soybean oil, tea seed oil, corn oil, rapeseed oil, evening primrose oil, camellia oil, and peach kernel oil. oil), coix seed oil, peanut oil, sunflower seed oil, grape seed oil, pond flower seed oil, rosemary oil, jojoba oil, macadamia oil, lavender oil, rosehip oil, mink oil and other animal and plant oils, tri(2-ethylhexanoin)glyceryl, isotridecyl isononanoate, isononyl isononanoate, hexadecyl 2-ethylhexanoate, isopropyl myristate, isopropyl palmitate, 2-ethylhexyl palmitate, octyldodecyl myristate, tricaprylyl, tri(caprylic / capric acid)glyceryl ) Glyceryl, diisostearate, glyceryl triisostearate, decaglycerol decaisostearate (polyglyceryl decaisostearate-10), propylene glycol dicaprate, neopentyl glycol dicaprate, polyglyceryl triisostearate, diisostearyl malate, neopentyl glycol diethylhexanoate, pentaerythritol tetraisostearate, pentaerythritol tetra(2-ethylhexanoate), dipentaerythritol pentaisostearate, dialkyl carbonate, bisethoxydiglycol cyclohexane-1,4-dicarboxylic acid Esters such as esters, dimer dilinoleyl hydrogenated rosin condensate, fatty acids such as oleic acid and isostearic acid, higher alcohols such as oleyl alcohol, 2-octyldodecanol, 2-decyltetradecyl alcohol, isostearyl alcohol, 2-hexyldecanol, dimethylpolysiloxane (dimethicone), methyl trimethicone, methylphenylpolysiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tetramethyltetrahydrocyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, tetramethyltetra(trifluoropropyl)cyclotetrasiloxane , pentamethylpenta(trifluoropropyl)cyclopentasiloxane, polyether-modified methylpolysiloxane, oleyl-modified methylpolysiloxane, polyvinylpyrrolidone-modified methylpolysiloxane and other silicone oils, perfluoropolyether, perfluorodecane, perfluorooctane and other fluorine-based oils, lanolin acetate, lanolin fatty acid isopropyl ester, lanolin alcohol and other lanolin derivatives, liquid ultraviolet absorbers such as 2-ethylhexyl methoxycinnamate and ethylhexyl salicylate, etc., and one or more of them can be used.
[0032] Among them, non-polar oils are preferred from the viewpoint of viscosity stability and emulsion stability. Examples thereof include hydrocarbons such as isododecane, isohexadecane, light isoparaffin, liquid paraffin (mineral oil), squalane, squalene, α-olefin oligomers, polybutene, liquid isoparaffin, heavy liquid isoparaffin, polyisobutene, and hydrogenated polyisobutene; and silicone oils such as dimethylpolysiloxane (dimethicone oil), methylpolytrimethylsiloxane, methylphenylpolysiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tetramethyltetrahydrocyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, tetramethyltetra(trifluoropropyl)cyclotetrasiloxane, pentamethylpenta(trifluoropropyl)cyclopentasiloxane, polyether-modified methylpolysiloxane, oleyl-modified methylpolysiloxane, and polyvinylpyrrolidone-modified methylpolysiloxane. One or more of these may be used. Particularly suitable are liquid paraffin (mineral oil) and dimethyl polysiloxane (dimethyl silicone oil). From the viewpoint of viscosity stability and emulsification stability, the content of component (C) in the composition of the present invention is preferably 1 to 10%, more preferably 1.5 to 6.5%. In addition, from the viewpoint of improving the oil-soluble active ingredient or viscosity, emulsification stability, the mass ratio of polar oil to non-polar oil ((polar oil) / (non-polar oil)) is preferably 0.5 or less, more preferably 0.3 or less. It should be noted that the component (C) liquid oil does not contain the component (D) oil-soluble active ingredient described later.
[0033] From the viewpoint of viscosity stability and emulsion stability, the IOB (inorganic-organic balance) of the polar oil used in the present invention is more preferably 0.05 to 0.8, and even more preferably 0.05 to 0.6. From the viewpoint of viscosity stability and emulsion stability, the IOB of the non-polar oil used in the present invention is preferably less than 0.05, and more preferably less than 0.03.
[0034] Here, IOB in the present invention is a value calculated by the following (Formula 1):
[0035] IOB = (ΣInorganic value / ΣOrganic value) …(Formula 1)
[0036] That is, IOB can be calculated as follows: based on the "inorganic value" and "organic value" set for various atoms and each functional group, the "inorganic value" and "organic value" of the atoms and functional groups that constitute organic compounds such as surfactants are integrated (see Yoshio Koda, "Organic Concept Map - Basics and Applications -", pages 11-17, Sankyo Publishing, published in 1984).
[0037] In addition, from the viewpoint of viscosity stability and emulsification stability, the mixed IOB of the liquid oil is preferably 0.8 or less, more preferably 0.6 or less, further preferably 0.4 or less, and particularly preferably 0.2 or less.
[0038] Here, the mixed IOB (IOB) of N liquid oils 总 ) is calculated using the following (Formula 2):
[0039] IBO 总 =IOB1·W1+IOB2·W2+…IOB N ·W N …(Formula 2)
[0040] IOB1, IOB2, IOB N :IOB of each liquid oil
[0041] W1, W2, W N : Weight fraction of each liquid oil (W1+W2+……+W N =1).
[0042] In the oil-in-water emulsion composition of the present invention, the molar ratio (A / B) of component (A) to component (B) is preferably 2.8 to 6, more preferably 2.8 to 4, from the viewpoint of viscosity stability and emulsification stability.
[0043] From the viewpoint of viscosity stability and emulsification stability, the content mass ratio of the total of components (A) and (B) to component (C) ((A+B) / C)) is preferably 0.3 to 0.75, more preferably 0.3 to 0.72.
[0044] The water content in the composition of the present invention is preferably 70 to 85%, more preferably 75 to 80%, from the viewpoint of viscosity stability and emulsion stability.
[0045] In the composition of the present invention, in addition to water, an aqueous solvent can be used. As an aqueous solvent, for example, lower alcohols such as ethanol and propanol, glycols such as propylene glycol, 1,3-butylene glycol, dipropylene glycol, 1,2-pentanediol, polyethylene glycol, glycerols such as glycerol, diglycerol, polyglycerol, etc. can be listed, and one or more of them can be used. Among them, from the viewpoint of viscosity stability and emulsification stability, 1,3-butylene glycol, dipropylene glycol, glycerol, diglycerol, polyglycerol are preferred. When using an aqueous solvent, from the viewpoint of viscosity stability and emulsification stability, it is preferred that the mass ratio (water / aqueous solvent) of the aqueous solvent relative to water is set to 5~20, more preferably 6~15.
[0046] The composition of the present invention may also contain component (D) oil-soluble active ingredients. Examples of oil-soluble active ingredients include tocopherol, carotenoids, retinol, ceramide, glycyrrhetinic acid and their esters, oil-soluble licorice, oil-soluble coix seed extract, oil-soluble rosemary extract, ubidecarenone, etc., and one or more of them can be used. As component (D), one or more of carotenoids and their esters are preferably selected. Examples of carotenoids include actinioerythrol, astaxanthin, bixin, canthaxanthin, capsanthin, capsanthin, β-8'-apo-carotenal (apocarotenal), β-12'-apo-carotenal, α-carotene, β-carotene, "carotene" (a mixture of α- and β-carotenes), γ-carotene, δ-carotene, β-cryptoxanthin, echinone, palm carotene, rutin, lycopene, violerythrin, zeaxanthin, fucoxanthin, antheraxanthin, and violaxanthin. Examples of carotenoid esters include esters in which a substance containing a hydroxyl group or a carboxyl group in a carotenoid forms one or more ester bonds with a fatty acid or a fatty alcohol. In particular, as component (D), one or more selected from astaxanthin and its esters are preferred. The fatty acid or fatty alcohol forming the ester preferably has a saturated or unsaturated straight or branched hydrocarbon chain having 8 to 24 carbon atoms. The content of the component (D) in the composition of the present invention can be appropriately set according to the type of the oil-soluble effective ingredient, for example, preferably 0.00001 to 1%, more preferably 0.00001 to 0.5.
[0047] In the composition of the present invention, in addition to the above-mentioned components, any components may be used as needed within the range that does not impair the effects of the present invention. Examples of such optional components include solid oils, powders, ultraviolet scattering agents, preservatives, and fragrances.
[0048] The composition of the present invention can be prepared by emulsifying and mixing the above-mentioned essential components and optional components as required according to a known method. For example, the oil phase containing components (A) to (C) and the water phase containing water are heated and dissolved separately, the oil phase is added to the water phase and emulsified and mixed by dispersion or the like, and then high-pressure emulsification treatment is performed using a microfluidizer, Ultimaizer, NanoVater, etc., thereby preparing the oil-in-water composition of the present invention.
[0049] From the viewpoint of viscosity stability and emulsion stability, the average emulsified particle size of the oil-in-water composition of the present invention is 160 nm or less, preferably 60 to 130 nm, and more preferably 70 to 120 nm. The average emulsified particle size can be adjusted by the pressure, treatment time, number of treatments, etc. of the high-pressure emulsification treatment. In this specification, the average emulsified particle size is a value measured by the method described in the Examples.
[0050] The water-in-oil type composition of the present invention is a composition that is excellent in viscosity stability over time, although it is in a liquid state, by making the average emulsified particle size below 160nm, and the reason is considered to be as follows. That is, in the preparation process of the water-in-oil type composition of the present invention, when α gel is formed by components (A) and (B), if the particle size of the emulsified droplets is large, a part of the α gel exists around the emulsified droplets and covers the emulsified droplets, but the α gel other than that is in a state of being dispersed in the continuous phase. It is believed that such remaining α gel forms a gel network over time and causes viscosity increase. In contrast, if the particle size of the emulsified droplets is reduced, the proportion of α gel existing around the emulsified droplets becomes higher, and if the average emulsified particle size is within the range of 160nm or less, most of the α gel covers the emulsified droplets, and the remaining α gel does not exist, so there will be no viscosity increase over time. When an anionic surfactant or a cationic surfactant other than the component (B) is used, even if the average emulsified particle size is set to 160 nm or less, an α-gel membrane structure covering the emulsified droplets is not formed, and thus the viscosity increases over time.
[0051] As described above, in the oil-in-water composition of the present invention, it is preferred that all or part of the emulsified droplets are coated with α-gel. The presence or absence of such an α-gel membrane structure coating the emulsified droplets (hereinafter sometimes referred to as "α-gel membrane structure") can be confirmed by differential scanning calorimetry (DSC) measurement. That is, when the emulsified droplets are large (for example, the average emulsified particle size is about 1 μm), one endothermic peak based on the remaining α-gel can be observed in the range of 58°C to 68°C in the DSC measurement, but as the particle size of the emulsified droplets decreases, while the endothermic peak gradually decreases, another endothermic peak based on the α-gel membrane structure coating the emulsified droplets can be observed on the lower temperature side. In this way, when two endothermic peaks based on the remaining α-gel and the α-gel membrane structure are observed in the range of 58 to 68°C in the DSC measurement, or when only one endothermic peak based on the α-gel membrane structure on the lower temperature side is observed, it is considered that there is an α-gel membrane structure coating the emulsified droplets. In addition, the presence of the α-gel membrane structure coating the emulsified droplets can also be confirmed by X-ray diffraction at 15 nm. -1 That is, when the interplanar spacing of α gel is about 4.15 Å, the interplanar spacing and wave number q satisfy the equation q = 2 × π (circular ratio) / d (interplanar spacing), so the wave number is 15 nm. -1 (See Non-Patent Documents 1 and 2, Figure 2 ). In addition, the presence of the α-gel membrane structure covering the emulsified droplets can also be confirmed by electron microscopic observation (refer to Figure 3 ).
[0052] It is believed that the presence of such an α-gel membrane structure covering the emulsion droplets contributes to improving the stability of the oil-soluble active ingredient. That is, when the oil-soluble active ingredient is contained in the water-in-oil emulsion composition, although the oil-soluble active ingredient is mainly present in the emulsion droplets, it will not always stay in the same position, but will produce molecular diffusion to the continuous phase, that is, the water phase (Ostwald ripening, refer to non-patent document 3), and the oil-soluble active ingredient will be degraded due to contact with water or the like of the continuous phase. In contrast, it is speculated that in the present invention, due to the presence of the α-gel membrane structure covering the emulsion droplets, the emulsion droplet interface becomes stronger, so that the contact with water or the like associated with the Ostwald ripening of the oil-soluble active ingredient can be suppressed, thereby improving the temporal stability of the oil-soluble active ingredient.
[0053] As described above, in the DSC measurement, in the range of 58°C to 68°C, one or both of the endothermic peaks based on the remaining α gel on the higher temperature side (60°C to 68°C) and the endothermic peaks based on the α gel membrane structure covering the emulsified droplets on the lower temperature side (58°C to 60°C) may be included. If the amount of heat (J / g) obtained from the area of all the endothermic peaks included in the temperature range of 58°C to 68°C is Q0, the amount of heat obtained from the area of the endothermic peaks based on the remaining α gel is Q1, and the amount of heat obtained from the area of the endothermic peaks based on the α gel membrane structure covering the emulsified droplets is Q2, then from the viewpoint of viscosity stability, the ratio Q1 / Q0 of the amount of heat obtained from the area of the endothermic peaks based on the remaining α gel to the amount of heat obtained from the area of all the endothermic peaks is preferably 0.7 or less, more preferably 0.2 or less, and even more preferably 0.1 or less. The heat quantities Q0, Q1, and Q2 obtained from the areas of the endothermic peaks are obtained as follows. That is, a DDSC curve is prepared as the differential value of the obtained DSC curve, and the temperature at which the DDSC curve begins to tilt is used as the base point. For the DSC curve, the peak area can be obtained by connecting the base points to the base points (base line). If the area (cm2) of all endothermic peaks contained in the temperature range of 58°C to 68°C is calculated, the peak area can be calculated. 2 ) was taken as A0, and the area (cm 2 ) is taken as A1, and the area (cm 2 ) is counted as A2, then the heat Q0, Q1, Q2 can be expressed by the following formula:
[0054]
[0055] Here, m i is the sample amount (g), c is the feed speed for recording data (cm / s), and P is the value of how many joules is equivalent to 1 cm in 1 second on the vertical axis of the DSC curve (J / cm·s).
[0056] From the viewpoint of viscosity stability and emulsification stability, the thickness of the α gel membrane in the α gel membrane structure is preferably 5 to 20 nm, more preferably 5 to 10 nm. In this specification, the thickness of the α gel membrane refers to the average thickness of α gel membranes of 100 emulsified droplets measured by electron microscope observation.
[0057] The oil-in-water emulsion composition of the present invention can be used as cosmetics, quasi-drugs, drugs, etc., and its form is a liquid form such as a cosmetic preparation such as a lotion, a beauty serum, a spray stock solution, a hair protectant, a liquid foundation, etc. In this specification, the liquid form means that the viscosity measured by the method described in the examples is 100 mPa·s or less, preferably 50 to 0 mPa·s. Example
[0058] The present invention will be described in more detail below with reference to Examples etc. However, the present invention is not limited to these Examples etc. in any way.
[0059] Test Example 1: Structural changes and stability caused by the particle size of emulsion droplets
[0060] The following formula and method were used to prepare water-in-oil type compositions with average emulsified particle sizes of 80 nm, 110 nm, 170 nm, and 1 μm. For each composition obtained, DSC measurement was performed under the following conditions. In addition, for the compositions with average emulsified particle sizes of 80 nm and 110 nm, X-ray diffraction was performed by the following method. In addition, for the composition with an average emulsified particle size of 110 nm, electron microscope observation was performed by the following method. The results are shown in Figures 1 to 3 middle.
[0061] (formula)
[0062] (Element) (%)
[0063] 1. Dimethyl silicone oil (25℃ 6mPa·s) 5.0
[0064] 2. Cetyl alcohol 1.5
[0065] 3. Sodium N-stearoyl-N-methyltaurate 1.0
[0066] 4. 1,3-Butanediol 12.0
[0067] 5. Methylparaben 0.15
[0068] 6. Phenoxyethanol 0.15
[0069] 7. Purified water 80.2.
[0070] (Preparation method)
[0071] A: Heat and dissolve No. 1 to 3 evenly.
[0072] B: Heat and dissolve No. 4 to 7 evenly.
[0073] C: Add A to B, emulsify and mix, then cool
[0074] D-1: C was subjected to a second high-pressure dispersion treatment (pressure of 130 MPa) using a microfluidizer to prepare an oil-in-water emulsion composition with an average emulsified particle size of 80 nm.
[0075] D-2: For C, high pressure dispersion treatment (pressure of 100 MPa) was performed three times using a microfluidizer to prepare an oil-in-water emulsion composition with an average emulsified particle size of 110 nm.
[0076] D-3: C was subjected to a second high-pressure dispersion treatment (pressure of 80 MPa) using a microfluidizer to prepare an oil-in-water emulsion composition with an average emulsified particle size of 170 nm.
[0077] D-4: C was stirred at 2000 rpm using a disperser to prepare an oil-in-water emulsion composition having an average emulsified particle size of 1 μm.
[0078] (Method for measuring average emulsified particle size)
[0079] Determination principle Dynamic scattering method
[0080] Solvent water
[0081] Measuring temperature 20℃
[0082] Measurement device Real-time nanoparticle size measurement device DelsaMax CORE
[0083] Light source 100 mW DPSS single longitudinal mode laser
[0084] Laser wavelength 658 nm
[0085] Detector Particle size determination Avalanche photodiode (APD)
[0086] Detector angle particle size measurement 90°
[0087] The particle size calculation method calculates the autocorrelation coefficient and the particle size through a multi-channel time delay (Multi-tau) method.
[0088] (DSC measurement method)
[0089] Equipment used: EXSTAR DSC6200 (manufactured by Seiko Instruments Inc.)
[0090] Reference: AIR
[0091] Heating rate: 5Cel / min,
[0092] Disk: P / N SSC000E031 AL15-CAPSULE
[0093] Analysis software: EXSTAR6000 Thermal Analysis / Rheology System (manufactured by Seiko Instruments Inc.).
[0094] (X-ray diffraction method)
[0095] Measuring equipment: SAXSess (manufactured by Anton Paar)
[0096] Measurement conditions: 25°C, 20 min.
[0097] like Figure 1 As shown, in the composition with an average emulsified particle size of 1 μm, an endothermic peak caused by the remaining α gel was found at around 61°C. This peak decreases as the particle size of the emulsified droplets decreases, but in the composition with an average emulsified particle size of 110 nm, in addition to this peak, a peak based on the α gel membrane structure covering the emulsified droplets was found at around 58°C. In the composition with an average emulsified particle size of 80 nm, the peak near 61°C disappeared, and only the peak near 58°C remained. This suggests that if the average emulsified particle size is 1 μm~170 nm, the α gel is mainly dispersed in the continuous phase as the remaining α gel, but if it is 110 nm, a state is formed in which the α gel covering the emulsified droplets and the remaining α gel coexist, and if it is 80 nm, the α gel mainly exists as a substance covering the emulsified droplets. The formation of the α gel membrane structure covering the emulsified droplets in the compositions with average emulsified particle sizes of 110 nm and 80 nm can also be seen from the X-ray diffraction at 15 nm. -1 There is a peak ( Figure 2 ) and electron micrographs ( Figure 3 ) was confirmed.
[0098] based on Figure 1 The heat amount Q0 obtained from the area of all endothermic peaks, the heat amount Q1 obtained from the area of the endothermic peak based on the remaining α gel, and the heat amount Q2 obtained from the area of the endothermic peak based on the α gel membrane structure covering the emulsified droplets were obtained using the above-mentioned analysis software EXSTAR6000, and the ratio Q1 / Q0 of the heat amount obtained from the area of the endothermic peak based on the remaining α gel to the heat amount obtained from the area of all endothermic peaks was calculated. The results are shown in Table 1.
[0099] [Table 1]
[0100] Average emulsified particle size <![CDATA[Q0]]> <![CDATA[Q1]]> <![CDATA[Q2]]> <![CDATA[Q1 / Q0]]> 80nm 1.91 0 1.91 0 110nm 1.10 0.15 0.33 0.136 170nm 1.20 0.94 0.04 0.783 1μm 1.82 1.82 0 1
[0101] The viscosity and emulsified state of each composition immediately after preparation and after storage at 50° C. for one month were evaluated according to the following measurement methods and criteria.
[0102] (Measurement / Evaluation Method of Properties (Viscosity))
[0103] The viscosity of each sample at 25°C was measured immediately after preparation and after storage at 50°C for 1 month, and evaluated according to the following criteria. The viscosity was measured according to the second method of the Cosmetic Raw Material Standard Viscosity Measurement Method using a Brookfield viscometer:
[0104] (Judgment): (Measurement result)
[0105] ◎: 10mPa·s or less
[0106] ○: More than 10 mPa·s and less than 100 mPa·s
[0107] ×: more than 100 mPa·s.
[0108] (Evaluation method of properties (emulsified state))
[0109] The emulsification state of each sample was visually confirmed immediately after preparation and after storage at 50°C for one month, and evaluated according to the following criteria:
[0110] (Judgment): (Status)
[0111] 0: No creaming or separation was found
[0112] △: Although no separation was observed, creaming was observed
[0113] ×: Separation was found.
[0114] [Table 2]
[0115]
[0116] It can be confirmed from Tables 1 and 2 that, compared with the test example with an average emulsified particle size of 170 nm and a Q1 / Q0 ratio of 0.783, the test example with an average emulsified particle size of 110 nm, a Q1 / Q0 ratio of 0.136 and the test example with an average emulsified particle size of 80 nm and a Q1 / Q0 ratio of 0 did not increase in viscosity even after being stored at 50°C for one month, but maintained a viscosity of less than 100 mPa·s, and had excellent viscosity stability over time.
[0117] Reference Example 1: Preparation of liposome-containing lotion
[0118] The lotion having the composition shown below was prepared by the following preparation method. The obtained lotion was observed under an electron microscope. The electron microscope photograph is shown in Figure 4 middle.
[0119] Reference example 1: Lotion
[0120] (Element) (%)
[0121] 1. Phospholipids 1.0
[0122] 2. Xanthan gum 0.1
[0123] 3. Carboxyvinyl polymer 0.05
[0124] 4. 1,3-Butanediol 20.0
[0125] 5. Glycerol 4.5
[0126] 6. Sodium hydroxide 0.02
[0127] 7. Parabens 0.1
[0128] 8. Trace amounts of spices
[0129] 9. Purified water balance.
[0130] (Preparation method)
[0131] A: Liposome a portion of Nos. 1, 8, and 9
[0132] B: Mix all remaining ingredients
[0133] C: Mix A and B to get lotion.
[0134] Figure 3 The emulsified droplets having the α-gel membrane structure of the present invention have an oil phase inside. Figure 4 The liposomes in the present invention do not have an oil phase inside, which is obviously different. In addition, since the liposomes form a multi-layer membrane, it can be seen that the membrane structure exists in multiple layers, but the α-gel membrane structure of the present invention does not have a layered membrane structure, which shows that the number of layered membranes is small.
[0135] In addition, it is known that the thickness of the α gel film of the present invention is about 3 molecular weights of a straight-chain saturated higher alcohol having 16 or more carbon atoms (the α gel film is a 3-molecule film of a higher alcohol). In order to form the α gel film structure, although it is also possible to form a 5-molecule film, a 7-molecule film, a 9-molecule film, etc., in addition, in that case, there is a possibility that a network structure is formed due to the increase in the number of films, thereby increasing the viscosity. Therefore, from the viewpoint of viscosity stability and emulsification stability, the film thickness of the α gel film is preferably 5 to 20 nm, more preferably 5 to 10 nm, and further preferably about 3 molecular weights of a straight-chain saturated higher alcohol having 16 or more carbon atoms (the α gel film is a 3-molecule film of a higher alcohol).
[0136] Examples 1 to 14 and Comparative Examples 1 to 12
[0137] The lotions of the compositions shown in Tables 3 to 6 below were prepared by the following preparation method. The viscosity and emulsified state of the obtained lotions were evaluated immediately after preparation and after storage at 50°C for 1 month according to the following measurement method and judgment criteria. In addition, the presence of the α-gel membrane structure covering the emulsified droplets was evaluated by the following method. The results are shown in Tables 3 to 6. It should be noted that the numerical values in the compositions of Tables 3 to 6 refer to %.
[0138] [Table 3]
[0139]
[0140] *1 Nikkol SMT (manufactured by Nikko Chemicals Co., Ltd.)
[0141] *2 Amisoft HA-P (produced by Xiangrong Industrial Co., Ltd.)
[0142] *3 Nikkol DDP-8 (manufactured by Nikko Chemicals Co., Ltd.).
[0143] [Table 4]
[0144]
[0145] [Table 5]
[0146]
[0147] [Table 6]
[0148]
[0149] <Preparation method>
[0150] (Examples 1, 7, 8, 10)
[0151] A: Heat and dissolve No. 1 to 15 evenly.
[0152] B: Heat and dissolve No. 16 to 19 evenly.
[0153] C: Add A to B for emulsified mixing
[0154] D: C was cooled and subjected to a second high-pressure dispersion treatment (pressure of 200 MPa) using a microfluidizer to obtain a lotion.
[0155] (Examples 2, 11-14)
[0156] A: Heat and dissolve No. 1 to 15 evenly.
[0157] B: Heat and dissolve No. 16 to 19 evenly.
[0158] C: Add A to B for emulsified mixing
[0159] D: C was cooled and subjected to a high-pressure dispersion treatment (pressure: 200 MPa) using a microfluidizer to obtain a lotion.
[0160] (Examples 3 to 6, 9, Comparative Examples 1 to 12)
[0161] A: Heat and dissolve No. 1 to 15 evenly.
[0162] B: Heat and dissolve No. 16 to 19 evenly.
[0163] C: Add A to B for emulsified mixing
[0164] D: C was cooled and subjected to a second high-pressure dispersion treatment (pressure of 100 MPa) using a microfluidizer to obtain a lotion.
[0165] <Evaluation method>
[0166] (Presence of α-gel membrane structure covering emulsified droplets)
[0167] For each lotion, an endothermic peak was observed by DSC measurement under the following conditions, and evaluation was performed based on the following criteria.
[0168] [DSC conditions]
[0169] Equipment used: EXSTAR DSC6200 (manufactured by Seiko Instruments Inc.)
[0170] Reference: AIR
[0171] Heating speed: 5Cel / min
[0172] Plate: P / N SSC000E031 AL15-CAPSULE.
[0173] [Judgment criteria]
[0174] (Judgment): (Status)
[0175] ◎: Only one peak was observed near 58°C
[0176] ○: Two peaks were observed at around 58°C and 61°C respectively.
[0177] △: Only one peak was observed near 61°C
[0178] ×: No peak observed
[0179] -: Unable to determine.
[0180] For the samples judged as ◎ or ○ by the above DSC measurement, the state of the α-gel membrane structure covering the emulsified droplets was observed by electron microscopy (refer to Figure 3 , the part surrounded by the circle in the figure). X-ray diffraction was performed (measurement equipment: SAXSess (manufactured by Anton Paar), measurement conditions: 25°C, 20 min), and the result showed that the -1 The peaks derived from the α-gel membrane structure were found (ref. Figure 2 ).
[0181] (Measurement / Evaluation Method of Properties (Viscosity))
[0182] The viscosity of each sample at 25° C. was measured immediately after preparation and after storage at 50° C. for 1 month, and evaluated according to the following criteria. The viscosity was measured according to the Cosmetic Raw Materials Standard Viscosity Measurement Method 2 using a Brookfield viscometer.
[0183] (Judgment): (Measurement result)
[0184] ◎: 10mPa·s or less
[0185] ○: More than 10 mPa·s and less than 100 mPa·s
[0186] ×: more than 100 mPa·s.
[0187] (Evaluation method of properties (emulsified state))
[0188] The emulsified state of each sample was visually confirmed immediately after preparation and after storage at 50° C. for one month, and evaluated based on the following criteria.
[0189] (Judgment): (Status)
[0190] 0: No creaming or separation was found
[0191] △: Although no separation was observed, creaming was observed
[0192] ×: Separation was found.
[0193] As shown in Tables 3 and 4, the presence of an α-gel membrane structure covering the emulsified droplets was found in all the lotions of Examples 1 to 14, and they were in a liquid state right after preparation. Even after being stored at 50°C for 1 month, the viscosity did not increase, but maintained below 100 mPa·s. In addition, separation or creaming did not occur, and a good emulsified state was maintained. In contrast, the presence of an α-gel membrane structure was not confirmed for the lotions of Comparative Examples 1 to 2, in which the average emulsified particle size was 170 nm or more, and an increase in viscosity over time was found. In addition, the lotions of Comparative Examples 3 to 5, in which a branched substance or a substance with less than 16 carbon atoms was used instead of a straight-chain saturated higher alcohol with 16 or more carbon atoms as component (A), were all found to be separated (initial separation) right after preparation. When a nonionic surfactant was used instead of component (B), initial separation also occurred (Comparative Example 6). When a cationic surfactant or an anionic surfactant other than component (B) was used, the presence of an α-gel membrane structure was not confirmed. Even if the average emulsified particle size was set to 160 nm or less, separation occurred after storage at 50°C for one month or the viscosity increased over time, and the emulsification stability and viscosity stability were poor (Comparative Examples 11 and 12). In addition, when the mass ratio of component (C) to the total of components (A) and (B) was outside the range of 0.3 to 0.75, the emulsification stability and viscosity stability were also poor (Comparative Examples 7 to 10).
[0194] Test Example 2: Stability test of oil-soluble active ingredients
[0195] The lotions having the compositions shown in the following Table 7 were prepared by the following preparation method. The stability of the oil-soluble active ingredient in the obtained lotions was evaluated by the following method.
[0196] [Table 7]
[0197]
[0198] *4 Astaxanthin-5C (manufactured by Oryza Oil & Fat Chemical Co., Ltd.)
[0199] *5 β-carotene (Sankyo Pharmaceutical)
[0200] *6 Kaneka Coenzyme Q10 (Kaneka).
[0201] (Preparation method)
[0202] A: Heat and mix No. 1 to 8 evenly to dissolve
[0203] B: Heat and dissolve No. 9 to 12 evenly.
[0204] C: Add A to B for emulsified mixing
[0205] D: C was cooled and subjected to a second high-pressure dispersion treatment (pressure of 130 MPa) using a microfluidizer to obtain a lotion.
[0206] (Stability evaluation method for astaxanthin, β-carotene and ubidecarenone)
[0207] For each lotion, the absorbance was measured immediately after preparation and after storage at 50°C for 1 month. Using a spectrophotometer UV-2500PC UV-VIS REDCORDING SPECTROPHOTOMETER (manufactured by SHIMADZU), a glass colorimetric cell with an optical path length of 10 mm and an optical path width of 10 mm was used, and purified water was used as a reference. The absorbance of astaxanthin was measured at a wavelength of about 480 nm, that of β-carotene at about 450 nm, and that of ubidecarenone at about 280 nm. The absorbance residual rate was calculated by the following formula, and the stability of astaxanthin, β-carotene, and ubidecarenone was evaluated according to the following standards:
[0208] Remaining absorbance rate (%) = (absorbance of the sample after storage at 50° C. for 1 month)×100 / (absorbance of the sample immediately after preparation).
[0209] <Stability Judgment Criteria>
[0210] (Judgment): (Absorbance Residual Rate)
[0211] ◎: The absorbance residual rate is more than 60%
[0212] ○: The absorbance residual rate is 50% or more and less than 60%
[0213] ×: The absorbance residual rate is less than 50%.
[0214] As shown in Table 7, in the lotion of Example 15, the fading of astaxanthin after storage at 50°C for one month was significantly suppressed compared with that of Comparative Example 13. This is considered to be because in Example 15, the α-gel membrane structure covered the emulsified droplets, and the emulsified droplet interface became stronger, thereby suppressing the contact with water and the like associated with the Ostwald ripening of astaxanthin, thereby suppressing the decomposition of astaxanthin, etc. On the other hand, in the lotion of Comparative Example 13, the α-gel membrane structure was not formed around the emulsified droplets, so the contact of astaxanthin with water and the like and the decomposition thereof occurred. Similarly, it was confirmed that β-carotene and ubidecarenone were also stably maintained after storage at 50°C for one month.
[0215] Test Example 3: Ratio of polar oil to non-polar oil and stability
[0216] The lotions of the compositions shown in Table 8 were prepared by the following preparation method. The viscosity and emulsified state of the lotions obtained were evaluated immediately after preparation and after storage at 50° C. for 1 month in the same manner as in Examples 1 to 14. In addition, the stability of astaxanthin was evaluated in the same manner as in Test Example 2. The results are shown in Table 6.
[0217] [Table 8]
[0218]
[0219] *7 HICALL K-230 (Kaneda)
[0220] *8 Myritol GTEH (BASF).
[0221] (Preparation method)
[0222] A: Heat and mix No. 1 to 5 evenly to dissolve
[0223] B: Heat and dissolve No. 6 to 9 evenly.
[0224] C: Add A to B for emulsified mixing
[0225] D: C was cooled and subjected to a second high-pressure dispersion treatment (pressure of 130 MPa) using a microfluidizer to obtain a lotion.
[0226] As shown in Table 8, the lotions of Examples 19 to 21 and Example 25 have better viscosity stability and emulsification stability after storage at 50°C for one month than the lotion of Example 27. In addition, the lotions of Examples 22 to 24 and Example 26 have better viscosity stability, emulsification stability and stability of oil-soluble active ingredients after storage at 50°C for one month than the lotion of Example 28. This is believed to be because the lower the content mass ratio of polar oil to non-polar oil ((polar oil) / (non-polar oil)), the lower the compatibility with straight-chain saturated higher alcohols, and the better the high-temperature time stability of the α-gel membrane structure.
[0227] Example 27: Lotion
[0228] (Element) (%)
[0229] 1. Dimethyl silicone oil (25℃ 6mPa·s) 4.5
[0230] 2. Ethylhexyl palmitate *9 0.5
[0231] 3. Cetearyl Alcohol 1.5
[0232] 4. Behenyl alcohol 0.8
[0233] 5. Cetearyl alcohol 0.8
[0234] 6. Sodium N-stearoyl-N-methyltaurate 0.7
[0235] 7. Glycerol 1.0
[0236] 8. 1,3-Butanediol 12.0
[0237] 9. Tripropylene glycol 0.5
[0238] 10. Citric acid 0.01
[0239] 11. Sodium citrate 0.01
[0240] 12. Purified water balance
[0241] *9 SALACOS P-8 (manufactured by Nisshin Oillio Group).
[0242] (Preparation method)
[0243] A: Heat and mix No. 1 to 5 evenly to dissolve
[0244] B: Heat and mix No. 6 to 12 evenly to dissolve
[0245] C: Add A to B for emulsified mixing
[0246] D: C was cooled and subjected to a second high-pressure dispersion treatment (pressure of 130 MPa) using a microfluidizer to obtain a lotion.
[0247] The lotion of Example 27 obtained as described above was in a liquid state of 30 mPa·s immediately after preparation, and had an average emulsified particle size of 80 nm, indicating a good emulsified state. The viscosity stability and emulsification stability at 50° C. after one month were also good.
[0248] Industrial Applicability
[0249] The oil-in-water emulsion composition of the present invention is excellent in viscosity stability and emulsification stability over time, although it is in a liquid state, and therefore can be used in liquid cosmetics, quasi-drugs, and the like.
Claims
1. A liquid oil-in-water composition comprising the following components (A) to (C): (A) a straight-chain saturated higher alcohol having 16 or more carbon atoms, (B) sodium N-stearoyl-N-methyltaurate, (C) Liquid oil; The molar ratio (A / B) of component (A) to component (B) is 2.8 to 6, and the mass ratio ((A+B) / C) of the total of components (A) and (B) to component (C) is 0.3 to 0.
75. in, The average emulsified particle size is 160 nm or less.
2. The liquid oil-in-water composition according to claim 1, wherein The viscosity at 25°C is 100 mPa·s or less.
3. The liquid oil-in-water composition according to claim 1 or 2, wherein The liquid oil as the component (C) is one or two selected from mineral oil and dimethyl silicone oil.
4. The liquid oil-in-water composition according to claim 1 or 2, wherein The content mass ratio of the polar oil to the nonpolar oil in the liquid oil of the component (C) ((polar oil) / (nonpolar oil)) is 0.5 or less.
5. The liquid oil-in-water composition according to claim 1 or 2, further comprising a component (D) an oil-soluble active ingredient.
6. The liquid oil-in-water composition according to claim 1 or 2, wherein: In the DSC curve measured by a differential scanning calorimeter, the ratio of the heat amount obtained from the endothermic peak area based on the remaining α-gel to the heat amount obtained from the total endothermic peak area included in the temperature range of 58 to 68° C. is 0.7 or less.
7. The liquid oil-in-water composition according to claim 1 or 2, further comprising an aqueous solvent, wherein the mass ratio of water to the aqueous solvent, that is, water / aqueous solvent, is 5 to 20.
Citation Information
Patent Citations
O / W-type emulsion composition
JP2001348325A
α gel intermediate composition, and production method of α gel-containing o / w emulsion cosmetic using composition thereof
JP2016014011A
Low viscosity water in oil-type emulsified composition and dermal agent for external use using the same
JP1997301847A